Detroit 1967 : Origins, Impacts, Legacies - Sugrue, Thomas J., 1962-; Stone, Joel (Joel Lagrou) (Book collections on Project MUSE., 2017)
"In the summer of 1967, Detroit experienced one of the worst racially charged civil disturbances in United States history. Years of frustration generated by entrenched and institutionalized racism boiled over late on a hot July night. In an event that has been called a "riot," "rebellion," "uprising," and "insurrection," thousands of people took to the streets for several days of vandalism, arson, and gunfire. Law enforcement was overwhelmed, and it wasn't until battle-tested federal troops arrived that the city returned to some semblance of normalcy. Fifty years later, native Detroiters cite this event as pivotal in the city's history, yet few completely understand what happened, why it happened, or how it continues to affect the city today. Discussions of the events are often rife with misinformation and myths, and seldom take place across racial lines. It is editor Joel Stone's intention with 'Detroit 1967: origins, impacts, legacies' to draw memories, facts, and analysis together to create a broader context for these conversations"--Jacket.